Pemberian tempe menurunkan kadar malondialdehyde (MDA) dan meningkatkan aktivitas enzim superoxide dismutase (SOD) pada tikus dengan aktivitas fisik tinggi - Harun, Iriyanti; Susanto, Hardhono; Rosidi, Ali (Jurnal Gizi dan Pangan, 2017)
The aim of this research was to analyze the influence of tempe giving to the oxidative stress in rats with high physical activities. This research was true experimental post-test only with control group design on 35 rats. The rats were given high physical activities and tempe treatments for 30 days. Those rats were divided into 5 group, which were: control 1 without giving tempe and supplement, control 2 with the giving of the commercial supplement, treatment 1 with giving 0.75 g tempe/200 g of body weight/day, treatment 2 with giving 1.5 g tempe/200 g of body weight/day and treatment 3 with giving 3 g tempe/200 g of body weight/day. At the end of this research, it was done the examination of the plasma MDA level by using TBARS method and activities of SOD enzyme using spectrofometry. The statistical analysis used One-way ANOVA Tests and Post Hoc LSD. The result showed that the tempe giving at various doses was significantly influenced to the reduction of MDA level (p<0.05) and also significantly influenced to the increasing activities of SOD enzyme (p<0.05). The giving of 3 g tempe was the most effective dose to the reduction of MDA level and the increasing activities of SOD enzyme. The conclusion was tempe could decrease the MDA level and increase the activities of SOD enzyme significantly in oxidative stress rats with high physical activities.